Docosahexaenoic Acid and Periodontitis in Adults: A Randomized Controlled Trial. (August 2014) - Naqvi, A.Z.; Hasturk, H.; Mu, L.; Phillips, R.S.; Davis, R.B.; Halem, S.; Campos, H.; Goodson, J.M.; Van Dyke, T.E.; Mukamal, K.J.
Periodontitis is a common chronic inflammatory disease initiated by bacteria, resulting in bone resorption, tooth loss, and systemic inflammation. Long-chain omega-3 fatty acids such as docosahexaenoic acid (DHA) reduce periodontitis in animals. We aimed to determine whether DHA supplementation with low-dose aspirin would reduce periodontitis in humans. We conducted a double-blind placebo-controlled parallel trial lasting 3 mo. Fifty-five adults with moderate periodontitis were randomized to 2, 000 mg of DHA or identical soy/corn oil capsules. All participants received 81 mg of aspirin but received no other treatments. We analyzed the primary outcome of per-pocket change in pocket depth using mixed models among teeth with pocket depth ≥5 mm. Secondary outcomes assessed with generalized estimating equations included gingival index, plaque index, and bleeding on probing. Gingival crevicular fluid samples were analyzed for changes in high-sensitivity C-reactive protein (hsCRP) and interleukins 6 and 1β (IL-6 and IL-1β). Plasma was analyzed for changes in systemic inflammatory markers, including hsCRP. We confirmed adherence with erythrocyte fatty acid measurement. Forty-six participants completed the trial. While similar at baseline, the proportion of DHA in red blood cell plasma membranes increased from 3.6% ± 0.9% to 6.2% ± 1.6% in the intervention group but did not change among controls. DHA supplementation decreased mean pocket depth (–0.29 ± 0.13; p = .03) and gingival index (–0.26 ± 0.13; p = .04). Plaque index and bleeding on probing did not change. Significant adjusted differences were found between DHA and control for both gingival crevicular fluid hsCRP (–5.3 ng/mL, standard error [SE] = 2.4, p = .03) and IL-1β (–20.1 pg/mL, SE = 8.2, p = .02) but not IL-6 (0.02 pg/mL, SE = 0.71, p = .98) or systemic hsCRP (–1.19 mg/L, SE = 0.90, p = .20). In this randomized controlled trial, aspirin-triggered DHA supplementation significantly improved periodontal outcomes in people with periodontitis, indicating its potential therapeutic efficacy (clinicaltrials.gov NTC01976806).